TD-DFT insight into photodissociation of the Co-C bond in coenzyme B12 - Kozlowski, Pawel M.; Liu, Hui; Kornobis, Karina; Lodowski, Piotr; Jaworska, Maria (Frontiers in Chemistry, 2014)
Coenzyme B12 (AdoCbl) is one of the most biologically active forms of vitamin B12, and continues to be a topic of active research interest. The mechanism of Co-C bond cleavage in AdoCbl, and the corresponding enzymatic reactions are however, not well understood at the molecular level. In this work, time-dependent density functional theory (TD-DFT) has been applied to investigate the photodissociation of coenzyme B12. To reduce computational cost, while retaining the major spectroscopic features of AdoCbl, a truncated model based on ribosylcobalamin (RibCbl) was used to simulate Co-C photodissociation. Equilibrium geometries of RibCbl were obtained by optimization at the DFT/BP86/TZVP level of theory, and low-lying excited states were calculated by TD-DFT using the same functional and basis set. The calculated singlet states, and absorption spectra were simulated in both the gas phase, and water, using the polarizable continuum model (PCM). Both spectra were in reasonable agreement with experimental data, and potential energy curves based on vertical excitations were plotted to explore the nature of Co-C bond dissociation. It was found that a repulsive 3(σCo-C → σ*Co-C) triplet state became dissociative at large Co-C bond distance, similar to a previous observation for methylcobalamin (MeCbl). Furthermore, potential energy surfaces (PESs) obtained as a function of both Co-CRib and Co-NIm distances, identify the S1 state as a key intermediate generated during photoexcitation of RibCbl, attributed to a mixture of a MLCT (metal-to-ligand charge transfer) and a σ bonding-ligand charge transfer (SBLCT) states.